Technical assistance for advancing National Adaptation Plans (NAPs): Tools, support, and access pathways from the Alliance of Bioversity International and CIAT - Rosenstock, Todd; Njuguna, Lucy; Chilambe, Pedro (2025)
This presentation showcases the various tools and data platforms developed by The Alliance that could be used to enhance the formulation, implementation and tracking of National Adaptation Plans (NAPs). The presentation was made at the Regional capacity-building workshop on NAPs for African Least Developed Countries and Small Island Developing States.